2000
DOI: 10.1023/a:1005623002979
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The specific interaction of muscle type creatine-kinase (MM-CK) with the myofibrillar M-line was demonstrated by exchanging endogenous MM-CK with an excess of fluorescently labeled MM-CK in situ, using chemically skinned skeletal muscle fibers and confocal microscopy. No binding of labeled MM-CK was noticed at the I-band of skinned fibers, where the enzyme is additionally located in vivo, as shown earlier by immunofluorescence staining of cryosections of intact muscle. However, when rhodamine-labeled MM-CK was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…Domains 7-8 of myomesin play a crucial role in the interaction with CK, and it has also been demonstrated that this interaction is not strictly species-specific (8,11,31). Since there is no published cDNA sequence of rabbit muscle myomesin, human myomesin fragment (hMy7-8) was cloned, expressed and purified to test the binding affinity of R-CK and O-CK with M-line protein.…”
Section: O-ck Unlike R-ck Cannot Interact With the M-line Protein Mmentioning
confidence: 99%
“…Domains 7-8 of myomesin play a crucial role in the interaction with CK, and it has also been demonstrated that this interaction is not strictly species-specific (8,11,31). Since there is no published cDNA sequence of rabbit muscle myomesin, human myomesin fragment (hMy7-8) was cloned, expressed and purified to test the binding affinity of R-CK and O-CK with M-line protein.…”
Section: O-ck Unlike R-ck Cannot Interact With the M-line Protein Mmentioning
confidence: 99%
“…Preparation of skeletal muscle fibres from rat psoas muscle and chemical permeabilization of the membranes were carried out according to the method described by Kraft et al [16]. The skinned skeletal muscle fibres were mounted on microscopic slides (in chambers made with PAP PEN, without covering the chambers) and incubated overnight at 4 • C in a drop (100 L) of the relaxing solution (10 mM imidazole, 2 mM magnesium chloride, 1 mM EGTA, 1 mM ATP, 20 mM creatine phosphate, 2 mM dithiothreitol, 106 mM potassium propionate; pH 7.5, T = 4 • C) containing 0.2 mg/mL of FITC-FBPase and then with 2 g/mL of rhodamine-phalloidin (for 1 h at room temperature).…”
Section: Isolation Of Single Skeletal Muscle Fibres and The Protein Ementioning
confidence: 99%
“…Glycolytic and Guanylate Metabolism in MAK ϭ/ϭ MuscleStudies in AK1 or M-CK single mutant mice and cell model systems suggest a compensatory interchange between the AK/CK circuits and the glycolytic machinery for energy production (4,6,16,33,39,48). We determined here that 18 O-metabolic labeling of Glc-6-P by hexokinase, the initial step in the glycolytic cascade, was significantly increased from 8.1 Ϯ 0.9% (n ϭ 6) in the wild-type to 18.9 Ϯ 0.9% (n ϭ 6) in MAK ϭ/ϭ…”
Section: Cellular Energetics In Resting Andmentioning
confidence: 99%
“…The interaction between AK-CK and glycolytic phosphotransfer systems is critical for energy supply and local ATP regeneration in different cell types (4,6,16,33,39,48,53). In muscles deficient in both AK1 and M-CK, glycolysis is probably the only remaining major cytosolic phosphotransfer circuit.…”
Section: Figmentioning
confidence: 99%